Lerak Detergen Campaign sebagai Utilization of Social Media Content dalam Green Awareness serta Green Lifestyle - Purnama, Susan; Pujianto, Anang Bambang; Sarifiyono, Aggi Panigoro; Hendriani, Ade Sintia (Jurnal Maps (Manajemen Perbankan Syariah), 2025)
This research aims to analyze the influence of social media content on green awareness and its impact on green lifestyle, specifically through the campaign of Lerak detergent as an environmentally friendly household product. The background of this study is the increasing urgency of environmental sustainability and the low level of public awareness regarding the use of natural-based cleaning products. The study uses a quantitative approach with a causal design, involving 300 respondents selected using cluster sampling across six regions in Indonesia. Data were collected through questionnaires, interviews, and field observations. The analysis was conducted using PLS-SEM. The results show that social media content has a significant positive effect on green awareness (path coefficient = 0.72; p < 0.001), which in turn significantly affects green lifestyle (path coefficient = 0.58; p < 0.001). Social media content also directly influences green lifestyle (path coefficient = 0.36; p < 0.001). These findings highlight the role of digital campaigns in increasing public understanding and adoption of sustainable consumption behaviors. Lerak detergent, as a local natural product, demonstrates strong potential when promoted through well-structured social media content.